2018
DOI: 10.1093/jee/tox347
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Insect Growth Regulators Methoxyfenozide and Pyriproxyfen and the Acaricide Bifenazate on Honey Bee (Hymenoptera: Apidae) Forager Survival

Abstract: The honey bee (Apis mellifera L. (Hymenoptera: Apidae)) contributes an essential role in the U.S. economy by pollinating major agricultural crops including almond, which depends entirely on honey bee pollination for successful nut set. Almond orchards are often treated with pesticides to control a variety of pests and pathogens, particularly during bloom. While the effects to honey bee health of some insecticides, particularly neonicotinoids, have received attention recently, the impact of other types of insec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…It inhibits the mitochondrial complex III in the spider mite T. urticae, and exhibits synergistic action of GABA response in Tu RDL GABAR . Recently, Fisher II et al (2018) reported that bifenazate could cause significantly negative effects on honeybee forager survival . Hence, the effect of bifenazate to Am RDL homopentamers was investigated in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits the mitochondrial complex III in the spider mite T. urticae, and exhibits synergistic action of GABA response in Tu RDL GABAR . Recently, Fisher II et al (2018) reported that bifenazate could cause significantly negative effects on honeybee forager survival . Hence, the effect of bifenazate to Am RDL homopentamers was investigated in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Some compounds, such as methoxyfenozide and flupyradifurone, were at high, albeit sublethal levels 29 . The IGRs methoxyfenozide and pyriproxyfen have been shown to reduce forager survival 4 . By October fewer pesticides were being detected overall, but the hives in MT landscapes were clearly being exposed www.nature.com/scientificreports www.nature.com/scientificreports/ to high levels of fungicides (chlorothalonil), herbicides (chlorthal-dimethyl and prodiamine) and IGRs (methoxyfenozide).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exposure to fenoxycarb affects the ability of colonies to overwinter, which reduces winter survival [58]. The juvenile hormone mimic, pyriproxyfen, affects synthesis and accumulation of vitellogenin (protein in hemolymph from which egg yolk is derived) in young worker bees [68] and negatively affects survival of honey bee foragers [69].…”
Section: Juvenile Hormone Mimicsmentioning
confidence: 99%
“…Ecdysone receptor antagonists/agonists are insect growth regulators that disrupt molting by inhibiting metabolism of the molting hormone, ecdysone, or they bind to ecdysone receptors, resulting in premature molting of larvae or nymphs, and eventually death [54,60,70,71]. Methoxyfenozide does not exhibit any harmful effects on honey bee larvae or adults [9] although Fisher et al [69] reported that methoxyfenozide negatively affected the survival of honey bee foragers. In general, tebufenozide has been shown to exhibit no direct or indirect harmful effects to honey bee colonies or queen development [58]; however, Abramson et al [56] found that tebufenozide negatively affected the learning behavior of honey bee adults.…”
Section: Ecdysone Receptor Antagonists/agonistsmentioning
confidence: 99%